Edukasi Kesehatan Partisipatif melalui Ceramah Interaktif dan Demonstrasi untuk Meningkatkan Pengetahuan Pencegahan Tuberkulosis pada Masyarakat RW 10 Kricak Tegalrejo: Participatory Health Education through Interactive Lectures and Demonstrations to Improve Tuberculosis Prevention Knowledge among Residents of RW 10, Kricak, Tegalrejo - Rika Rokhim Septianingsih; Almerio Alfares Laurensius Yekbat; Davina Azalya Arvi; Fitri Nur Aini; Aulia Komala Latri; Muhammad Dzaky Hilmy; Gita Mayang Pramono Putri; Tasya Annisa; Yeheskhiel Mie Murutop; Ikhwan Mumtaz Hanif; Yusniarita Yusniarita; Sarka Ade Susana (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2025)
Tuberculosis (TB) remains a public health problem, particularly in densely populated areas with inadequate ventilation. Limited community knowledge regarding TB transmission, prevention, treatment adherence, and stigma toward patients may increase the risk of transmission. This community service activity aimed to improve community knowledge of tuberculosis prevention and treatment adherence. The activity used health education with a participatory approach through interactive lectures, discussions, question-and-answer sessions, and demonstrations. The activity was conducted in RW 10 Kricak Tegalrejo in April 2026 and involved 10 participants. Evaluation was conducted using pretest and posttest assessments to measure changes in knowledge, supported by observation of TB prevention practices. The results showed that the participants' mean knowledge score increased from 78% at pretest to 96% at posttest, representing an 18% increase. Understanding of TB-related stigma also improved from 70% to 90%. All participants (100%) showed an increase in scores, and 90% achieved a minimum posttest score of 80%. Participants were also able to correctly demonstrate cough etiquette and proper mask use. Participatory health education can improve community knowledge of TB prevention and support the development of preventive attitudes and skills at the community level.